Average saturated fatty acids daily intake in Sarajevo University students (Journal of Health Sciences, 2014)
Introduction: There are wide variations in diet patterns among population subgroups. Macronutrients content analyses have become necessary in dietary assessment. The purpose of this study is to analyze dietary saturated fatty acids intake in students, detect differences between men and women, and compare with nourish status and nutrition recommendations.Methods: A cross-sectional survey of 60 graduate students was performed during the spring 2013, at the Sarajevo University. Food-frequency questionnaire was conducted during seven days. Body mass index was used to assess students' nourish status. Statistical analyses were performed using the Statistical Package for Social Sciences software (version 13.0).Results: Mean age of males was 26.00±2.72, and of females was 27.01±3.93 years. The prevalence of overweight was more common among males compared to females (55.56% vs. 6.06%). Median of total fat average intake for men and women was 76.32(70.15;114.41) and 69.41(63.23;86.94) g/d, respectively. Median of saturated fatty acids average intake for men and women was 28.86(22.41;36.42) and 24.29(20.53;31.60) g/d, respectively. There was significant difference in average intake of total fat between genders (Mann-Whitney U test: p=0.04). Macronutrient data were related to requirement of reference person. Total fat intake was beyond recommended limits in 37.04% of males and 54.55% of females. Saturated fatty acids intake was beyond the upper limit in 55.56% of males and 51.52% of females.Conclusion: Diet pattern of the average student is not in accordance with the recommendations of saturated fatty acids contribution as a percentage of energy.